A study on use of miniature dielectric compound parabolic concentrator (dCPC) for daylighting control application - Yu, Xu; Su, Yuehong; Zheng, Hongfei; Riffat, Saffa (Elsevier, 2014)
Low-concentration solid dielectric compound parabolic concentrator (dCPC) and its variations have been widely regarded as an attractive solution to reduce the cost of a photovoltaic (PV) system, particularly for building-integrated application. Different from a mirror CPC, a dCPC allows the light beyond its acceptance angle to penetrate through its lateral surface. This escaped light could be actually used for daylighting, so the dCPC offers a potential for combined PV and daylighting application suitable for the atrium buildings or large green houses. In the modern buildings, an advanced daylighting system such as prismatic panels is used to balance between harvesting daylight and preventing excessive solar heat gain. In contrast, this study aims to evaluate the advantage of the miniature solid dCPC over common prismatic structures according to their daylight transmittance values under both standard and real sky conditions. A commercial optical analysis software PHOTOPIA is firstly used to compare the daylighting control performance between a dCPC rod and two common prismatic elements. The effect of solar altitude and azimuth angles changing with time is considered. A preliminary test under a solar simulator and a real sky condition is also introduced to provide experimental evidence regarding the advantageous feature of a dCPC rod for daylighting control.